Pengaruh Kualitas Produk Dan Persepsi Harga Terhadap Minat Beli Konsumen Pada Brand Local Sepatu Compass (studi Kasus Pada Pengguna Sepatu Compass Di Kab. Bekasi) - Ridwal, Ridwal; Irwansyah, Iwan; Septa Zahran, Wahidin; Puspa Arum, Suryawati (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine the extent to which Product Quality and Price Perception influence the Purchase Intention of consumers for Compass shoes in Bekasi Regency, both individually and simultaneously. The sample of this study consisted of 150 respondents who are users of Compass shoes. The method used in this study is descriptive quantitative. The results of the study show that Product Quality has a 61.9% influence on Purchase Intention, and the t-test indicates a positive and significant influence. Price Perception has a 53.1% influence on Purchase Intention, and the t-test indicates a positive and significant influence. The simultaneous test results indicate that Product Quality and Price Perception collectively have a 66.0% influence on Purchase Intention. Based on the Anova F-test, the calculated Sig. value is 0.000 < 0.05, thus it can be concluded that Product Quality (X1) and Price Perception (X2) simultaneously influence Purchase Intention (Y).